Setting Health-Care Priorities: A Reply to Massimo Reichlin (Diametros, 2021)
This is a short reply to Professor Reichlin’s comment on my book Setting Health-Care Priorities. What Ethical Theories Tell Us. The version of prioritarianism I rely on in the book is defended as the most plausible one. The general claim that there is convergence between all plausible theories on distributive justice is also defended with regard to assisted reproduction, disability, and enhancement.
Keywords: priority setting; prioritarianism; assisted reproduction; disability; enhancement